2023
DOI: 10.1128/spectrum.05194-22
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Honey Bee Digestive Tracts by Environmental Yeast Lachancea thermotolerans Is Naturally Occurring, Temperature Dependent, and Impacts the Microbiome of Newly Emerged Bees

Abstract: Although many fungal species are found in association with honey bees and their broader environment, the effects of these interactions on honey bee health are largely unknown. Here, we report the discovery that a yeast commonly found in the environment can be found at high levels in honey bee digestive tracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…The manipulability of both microbiome and body temperature in a host with a predominantly endothermic life history strategy makes honey bees a useful system to explore the value of endothermy as a reinforcer of symbioses and symbiont-mediated defense against parasites. Prior work has shown that high (35 °C) temperatures increase resistance of honey bees to colonization by heat-sensitive environmental yeasts relative to cooler (29 °C) temperatures, consistent with the seasonal appearance of yeasts during colder weather in field-collected forager bees (73). On the other hand, high (35 °C) temperatures enhanced growth of and gut colonization by the core symbiont S. alvi in bumble bees relative to low (28-29 °) temperatures (64).…”
Section: Discussionsupporting
confidence: 63%
“…The manipulability of both microbiome and body temperature in a host with a predominantly endothermic life history strategy makes honey bees a useful system to explore the value of endothermy as a reinforcer of symbioses and symbiont-mediated defense against parasites. Prior work has shown that high (35 °C) temperatures increase resistance of honey bees to colonization by heat-sensitive environmental yeasts relative to cooler (29 °C) temperatures, consistent with the seasonal appearance of yeasts during colder weather in field-collected forager bees (73). On the other hand, high (35 °C) temperatures enhanced growth of and gut colonization by the core symbiont S. alvi in bumble bees relative to low (28-29 °) temperatures (64).…”
Section: Discussionsupporting
confidence: 63%
“…To determine whether bleomycin treatment impacts the microbiome, we used primer sets amplifying the 16S rRNA region of all bacteria as well as sets that amplify the species-specific 16S rRNA region of the most predominant species in uninoculated cage-reared bees, Gilliamella apicola ( 19 ). Combining the data from three independent trials, we found that bleomycin (0.613 µg/mL) had no statistically significant effect on total bacteria levels or on the levels of G. apicola in the midgut ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For examining levels of total bacteria and one specific bacterial species of the digestive tract microbiome ( Gilliamella apicola ), a similar assay was performed using universal 16S rRNA primers and species-specific 16S rRNA primers from reference ( 18 ) in conjunction with the honey bee ATP5a gene. G. apicola was chosen as the single bacterial species to investigate in more detail because previous studies have found that this is the predominant species in uninoculated cage-reared bees ( 19 , 20 ), while other bacterial subsets are typically highly variable and at very low levels.…”
Section: Methodsmentioning
confidence: 99%
“…We highlight the better performance of wild strains at low temperatures, which may improve survival in wild environments such as those associated with insects or subboreal locations (Hranilovic et al, 2017). It has been verified that colonization of bee digestive tracts by L. thermotolerans is associated with lower temperatures (Kogan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%